Effect of Key Modification on Roll Former to Rim Production Process - Iwan Nugraha Gusniar; Marga Rizqi Wilanno (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2022)
A Roll former is a tool used to form the surface of the rims. Roll former often experiences anomalies in its movement that make the formation of the rim after going through the roll former not so good. The anomaly was caused by a crack in the keys roll former. To deal with this, simulation analysis and modification of the design are carried out. The simulation was done using CAE with SolidWorks software. In the simulation, the research object used bolts with AISI 4130 material and keys with AISI 1045 material. Simulation is used to obtain the maximum stress and tensile stress, and displacement of the key roll former. Based on the results of the research was found that the roll formers locks with keys have better strength than the roll former locks that use bolts. From these results, the roll formers locks are modified from the one that used bolts for keys. Roll Former merupakan alat yang digunakan untuk membentuk permukaan pelek. Roll former seringkali mengalami anomali pada gerakannya yang membuat hasil pembentukan pelek setelah melalui roll former tidak begitu baik. Anomali tersebut disebabkan oleh crack pada pengunci roll former. Untuk menangani hal tersebut maka dilakukan analisis secara simulasi dan modifikasi pada desain. Simulasi dilakukan dengan menggunakan CAE dengan perangkat lunak SolidWorks. Pada simulasi tersebut objek penelitian yang digunakan adalah baut dengan material AISI 4130 dan pasak dengan material AISI 1045. Simulasi digunakan untuk memperoleh tegangan maksimum, tegangan tarik, dan perubahan bentuk pada pengunci roll former. Berdasarkan hasil penelitian didapatkan bahwa pengunci roll former dengan pasak memiliki kekuatan yang lebih baik dari pengunci roll former yang menggunakan baut. Dari hasil tersebut maka pengunci roll former dimodifikasi dari yang awalnya menggunakan baut menjadi pasak.